Evaluating the work of private schools from the viewpoint of principals of private and public primary schools - Kamal Muni Emira Emira ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
Asummary of current research examining the pros and cons of private schools in Basra Directorate of Education for the purpose of evaluation and research aims to find out the views of the government and private school administrators in this regard. The research sample primary managers of government     تقويم عمل المدارس الأهلية من وجهة نظرمديري المدارس الابتدائية الأهلية والحكومية   كمال موني طاهر الأمارةالكلية التربوية المفتوحة/ مركز البصرة     and private schools in the province center have been identified where thesample pulled by 1% from the research community.The researcher used percentages, the weighted average, the weight percentile, and T- test for two independent samples of equal statistical means.The results showed that there were no statistically significant differences between the government and private schools and managers confirmed the existence of a positive assessment of the civil schools. Researcher recommended the expansion of private schools experience and the development of a fixed system for granting holidays, as well as the application of the laws of the Ministry of Education and coverage of educational guide services.There are some negatives must concern themselves with the Ministry of Education and small schools, control civil headmaster success rates to raise them and attract large numbers of students at the expense of quality.